Physical-chemical characterisation of an alum-based water treatment sludge in different raw water turbidity scenarios - Camilo C. Castro-Jiménez; Julio C. Saldarriaga-Molina; Edwin F. García (Heliyon, 2024)
Characterisation of the water treatment sludge (WTS) generated in drinking water treatment plants (DWTPs) is crucial to define alternatives for its adequate management, including potential reuse options. To define these alternatives, it is necessary to evaluate rainfall seasonality effect on WTS production and its physical and chemical characteristics. This study assessed the production and characterisation of four types of alum-based WTS. The WTS was generated in a pilot-scale system from different raw water turbidities (i.e., low: <5 NTU, medium: 5–10 NTU, high: ≥10 NTU, and very high turbidity: ∼300 NTU) and coagulant doses. To estimate WTS production, mathematical models based on variables such as raw water turbidity, coagulant dosage, and organic matter removed were used. The WTS characterisations included physical (solids and particle size distribution), chemical (metallic oxides, pH, mineral phases), and surface properties (functional groups and zero-charge point pH). The modified Kawamura model presented the best fit (R2 = 1.0, RMSE = 0.1062 and the lower Akaike Information Criterion) for the estimation of WTS production, indicating that at the DWTPs, it is possible to make sludge production projections using only two simple variables: coagulant dose and the raw water turbidity. The four types of WTS consist mainly of amorphous materials (45–65 %), featuring some mineral phases and exhibiting high contents of Al (Al2O3: 30–34 %), Si (SiO2: 21–26 %) and Fe (Fe2O3: 11–13 %). Nevertheless, very high turbidity WTS shows variations in its characteristics, notably a heightened content of clays. As a result of the high concentrations of Al and Fe, the WTS has the potential to be used as coagulants or for the recovery of coagulants, especially low turbidity WTS, which is produced from water with low turbidity and organic matter. The presence of aluminium–silicate clays and the surface functional groups of the silica network suggest that WTS, particularly very high turbidity WTS, also has the potential to be raw materials for generating adsorbents. The potential applications of WTS in coagulation and adsorption can be leveraged in wastewater treatment, promoting the circular economy in the water sector.